2015
DOI: 10.1088/1468-6996/16/1/014402
|View full text |Cite
|
Sign up to set email alerts
|

Giant multiferroic effects in topological GeTe-Sb2Te3superlattices

Abstract: Multiferroics, materials in which both magnetic and electric fields can induce each other, resulting in a magnetoelectric response, have been attracting increasing attention, although the induced magnetic susceptibility and dielectric constant are usually small and have typically been reported for low temperatures. The magnetoelectric response usually depends on d-electrons of transition metals. Here we report that in [(GeTe)2(Sb2Te3)l]m superlattice films (where l and m are integers) with topological phase tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
93
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 35 publications
1
93
3
Order By: Relevance
“…By contrast, in a PCM cell based on a GST alloy, a high RESET current is needed to melt the material prior to amorphization. iPCMs open numerous opportunities for multilevel storage, hybrid devices combining resistive and magnetic memories, logic gate devices, and also devices for THz pulse detection . Incorporation of SLs in iPCM devices by using ULSI microelectronics technology has been demonstrated for large density memory arrays…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in a PCM cell based on a GST alloy, a high RESET current is needed to melt the material prior to amorphization. iPCMs open numerous opportunities for multilevel storage, hybrid devices combining resistive and magnetic memories, logic gate devices, and also devices for THz pulse detection . Incorporation of SLs in iPCM devices by using ULSI microelectronics technology has been demonstrated for large density memory arrays…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, several superlattice structures including GeTe/Sb 2 Te 3 have been theoretically predicted to exhibit unusual properties forming topological insulators or Dirac semimetals, leading to the experimental confirmation of unusual magnetic properties despite the lack of magnetic elements. [12][13][14][15] The most widely used techniques to fabricate 2D chalcogenides are exfoliation from a bulk single crystal, chemical vapor deposition (CVD), and molecular beam epitaxy (MBE). [16][17][18][19][20][21] However, the area of films that can be fabricated by exfoliation is limited and sample sizes are not uniform.…”
mentioning
confidence: 99%
“…Interfacial PCMs (iPCMs)9 or chalcogenide superlattices consisting of Sb 2 Te 3 and GeTe multilayers are a promising candidate for data storage devices with reduced energy consumption since reversible transition between SET and RESET states is assumed to be constrained by motion of atoms in 1D instead of 3D as in the case of conventional PCM devices. Thus, the switching mechanism of iPCMs is determined by the local atomic arrangement in distinct layers10111213, which also defines the electronic properties of the materials14. In particular, theoretical simulations showed that iPCMs can be a 3-D topological insulator15 or a Dirac semimetal11.…”
mentioning
confidence: 99%